Нові дані про поширення рідкісних видів Galanthus L. і Arum L. на Придніпровській височині - Мельник, В.І.; Діденко, С.Я.; Діденко, І.П.; Галушко, О.С. (Український ботанічний журнал, 2013)
Выявлены новые местонахождения редких, занесенных в «Красную книгу Украины», видов Galanthus plicatus M. Bieb, G. nivalis L. и регіонально редкого вида Arum besserianum Schott. на Приднепровской возвышенности (Черкасская обл.). Описаны условия их местообитаний и состояние популяций, предложены рекомендации по улучшению охраны этих редких видов. New localities for the following rare species in Prydniprovska Upland are reported: Galanthus plicatus M. Bieb., G. nivalis L. (Amaryllidaceae) listed in the Red Data Book of Ukraine (2009) and Arum besserianum Schott, a rare species in Cherkasy Region. The habitats and population status for each species are described. Recommendations on their conservation are provided.